Analisis Kinerja Keuangan Koperasi Unit Desa Minasari Pangandaran Berdasarkan Perhitungan Rasio Keuangan - Hilmy Rizal Hidayat; Jouzar Farouq Ishak (Jurusan Akuntansi Politeknik Negeri Bandung, 2021)
The purpose of this study was to determine and assess the financial performance of the Minasari Village Unit Cooperative based on an analysis of the ratio of liquidity, solvency, profitability, and activity. Financial ratio analysis is used as an analytical method in this study. Overall the results of this study indicate that the financial performance of the Minasari Village Unit Cooperative is good, it can be seen from the level of liquidity to short-term debt is good, the level of solvency is good, the level of profitability of capital and assets is quite good, but the level of asset turnover activity can be said not good because it is still far below the standard. For the Minasari Pangandaran Village Unit Cooperative, it is expected to maintain this good liquidity, solvency, and profitability ratio and increase the asset turnover activity ratio by utilizing the assets owned more effectively and efficiently.